A green route for methanol carbonylation. Issue 20 (3rd October 2017) - Ni, Youming; Shi, Lei; Liu, Hongchao; Zhang, Wenna; Liu, Yong; Zhu, Wenliang; Liu, Zhongmin
Abstract : Halide-free and noble metal-free pyridine-modified H-mordenites exhibit high stability and selectivity in methanol carbonylation to acetic acid. Abstract : Acetic acid is one of the most important bulk commodity chemicals and is currently manufactured by methanol carbonylation reactions with rhodium or iridium organometallic complexes and halide-containing promoters named Monsanto or BP Cativa™ homogeneous processes, respectively. Developing a halide-free catalyst and a heterogeneous process for methanol carbonylation is of great importance and has recently attracted extensive research attention. Here, we report a green route for direct synthesis of acetic acid via vapor-phase carbonylation of methanol with a stable, selective, halide-free, and noble metal-free catalyst based on pyridine-modified H-mordenite zeolite. Methanol conversion and acetic acid selectivity can reach up to 100% and 95%, respectively. Only little deactivation is observed during the 145 hour reaction.